Dampak Pandemi Covid 19 terhadap UKM Konveksi di Kelurahan Tegal Sari III, Medan Area, Kota Medan - Faudunasokhi Telaumbanua (Lembaga Riset Ilmiah, Yayasan Mentari Meraki Asa, 2022)
Changes in people's behavior during the pandemic have an impact on all business sectors, one of which is the convection business. This change is because there is a ban for school children, office work is also carried out boldly, as well as a ban on face-to-face interactions with small traders. Therefore, there was a decrease in the number of sales to convective business actors due to the impact of the Covid -19 pandemic. The decline in sales was due to the difficulty of marketing convection products in Tegal Sari III Village in Bromo Village. The purpose of the study was to determine the impact of the Covid 19 pandemic on convection. This study uses a descriptive approach. The method of data collection uses interviews, observation, and documentation. The result of the research is that sales convection in Tegal Sari III Village has decreased, including in March to December 2020, namely in shirt convection sales decreased to 52.6%, school bag convection 54.4%, mukena 53.6%, school shoes 53 .2%, and jeans 44.1%. it can be concluded that sales have decreased drastically when compared to sales in 2019 before the pandemic. However, the way of marketing has changed, which was previously marketed conventionally with the online pandemic. Thus, it is hoped that future research can examine what strategies are applied to increase sales business actors in Tegal Sari III Village, Medan.